Działalność duszpasterska i muzyczna ks. Roberta Gajdy na ziemi kłodzkiej - Prasał, Andrzej (Studia Pastoralne, 2026)
The article deals with the activites of Father Robert Gajda (1890–1952) in Kłodzko land in the years 1917–1924. It is based on heretofore unknown source materials from the priest’s personal file in the record office of the former Grand Deanery of Kłodzko as well as mentions in the local press. Father Gajda started his pastoral activities in the county of Kłodzko in mid 1917, when he became chaplain in Ludwikowice Kłodzkie. There he gained a reputation as a zealous priest loved by his parishioners. In the years 1919–1924 he was chaplain in Stary Wielisław, where he combined his priestly duties with academic studies at the Silesian Conservatory in Wrocław as well as activities as a composer. He created 16 of his first works in Stary Wielisław, the most well-known among them being Missa ”Regina pacis”. Those works were mostly performed in Stary Wielisław, but also in Kłodzko and Lądek-Zdrój. Father Gajda also created an arrangement for choir and orchestra to be performed at the mystery plays of the Lord’s Passion in Gorzanów in 1922. He was also involved in the activities of the Cecilian Society of the County of Kłodzko.